A LDO regulator with weighted current feedback technique for 0.47nF-10nF capacitive load - Tan, Xiao Liang (2014)
A Weighted Current Feedback (WCF) technique for output capacitorless low-dropout (OCL-LDO) regulator is presented in this paper. Through feedback of a weighted current, the WCF permits smart management of the output impedance as well as the gain from the inter-gain stage. Based on the Routh-Hurwitz stability criterion, the WCF can avoid the right-half plane (RHP) pole and push the left-half plane (LHP) non-dominant complex pole pair to a higher frequency. Besides, it provides good regulator loop gain and fast transient response. Validated by UMC 65 nm CMOS process, the simulation and measurement results have shown that the WCF LDO regulator can operate at a load capacitance (CL) range from 470 pF to 10 nF with only 3.8 pF compensation capacitor. At a supply of 0.75 V and a quiescent current of 15.9 μA, the proposed circuit can support a maximum load current (IL) of 50 mA. When IL switches from 0 to 50 mA in 100 ns, the output can settle within 400 ns for the whole CL range. For a case of single capacitor (CL 470 pF), the settling time is only 250 ns. The comparison results have shown that the WCF LDO regulator offers a comparable or better transient figure-of-merit (FOM) and additional merit to drive wide load capacitance range.